(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Pharmaceutical companies are one of the foundations of a country's health because they play an important role in the supply chain of medicines used by hospitals and other health institutions. Pharmaceutical company governance rarely gets attention and it is necessary to conduct deeper studies, especially with regard to corporate governance and earnings management practices of pharmaceutical companies in Indonesia. This type of research is included in quantitative research, namely research that uses a process approach to collect and analyze numerical data. The sampling technique is judgment sampling, which is non-probabilistic. Samples were obtained from pharmaceutical company in the Indonesia stock exchange (IDX). The companies that were chosen were those that were listed on the stock exchange for the required minimum observation times. Public listed pharmaceutical company in Indonesia from 2015 to 2017 were the inclusion criteria. Regression coefficient analysis will be the third statistical analysis. The purpose of this analysis is to evaluate the significance of the research model as well as the variable's importance. The results of this study explain that board size, independent commissioners, and earnings management have a significant effect on firm value. The mediating role of earning management on the effect of corporate governance on corporate value is successful and significant. Pharmaceutical companies need to know the benefits of board size and independent commissioners in their impact on company value. Earnings management has been proven successful in mediating corporate governance in increasing the value of pharmaceutical companies to a higher level. Reducing earnings management practices is proven to increase investor confidence so that it will increase the company's value in the market through the company's stock price.